An aluminium nitride based multilayer structure for Love mode surface acoustic wave devices. (24th September 2020) - Aslam, Muhammad Zubair; Jeoti, Varun; Manzoor, Shahid; Hanif, Mehwish; Junaid, Muhammad
Abstract: Love mode surface acoustic wave (SAW) devices are very useful for sensing in liquid environments. Earlier work on such devices mainly made use of zinc oxide (ZnO) thin films on silicon (Si) or silicon dioxide ( Si O 2 ). However, using them for sensing still required protection from contamination from zinc (Zn) in the form of some additional passivation layer. In this work, the objective has been to study an aluminium nitride (AlN)-based multilayer structure that is able to generate SAW Love modes very efficiently. A layer of Si O 2 on top of the AlN layer does the trick. A 3D finite element method simulation analysis of the proposed structure ( Si O 2 / AlN 11 2 ˉ 0 / Si O 2 / Si  100 ) is accordingly performed, and phase velocities, electromechanical coupling coefficients and frequency shift due to mass loading are simulated as a function of the normalized thicknesses of AlN and Si O 2 films. It is shown that the optimal normalized thickness identified to be h s 2 / λ = 0.18, h AlN / λ = 0.45 with AlN c -axis orientation of 30 o, and the maximum value of the electromechanical coupling coefficient k 2 = 0.58% can be achieved. Even though the value of k 2 is comparable to ZnO-based Love mode devices, the phase velocity is 1.5 times higher (5530 m s −1 compared to 3652 m s −1 ). Equally importantly, it is seen that the frequency shift due to mass loading of deionized water (the AlN-based multilayer Love mode sensor) is much higher for that using the ZnO-based multilayer Love mode sensor.